From the cart to the base for big bags. Notes about the collective construction of a tool to improve the quality of the work of Environmental Recuperators of the Autonomous City of Buenos Aires - Schamber, Pablo J. (2020)
This article describes an ongoing research experience about the waste management system of the Autonomous City of Buenos Aires (CABA) and other municipalities in the metropolitan area of Buenos Aires. During the fieldwork, some inconveniences were detected in the work process that involved cartoneros cooperatives. The article tries to give visibility to these disadvantages. Still, it mainly aims to describe the process by which, with the participation of different actors, a very simple tool was designed, developed, and tested. The aim is to contribute to the debate and reflection on the role of academic research and transfer activities within the framework of the commitment to the social groups that are the object/beneficiaries of these activities.